Student Perspectives on E-Learning in a Malaysian Medical College One Year into the COVID-19 Pandemic: A Cross-Sectional Study - Sylvia Wei Wei Kong; Jade Lene Yong; Sabrina Pei Yee Cheong; Edmund Liang Chai Ong (University Library System, University of Pittsburgh, 2023)
Background: During the coronavirus disease 2019 (COVID-19) pandemic, most in-person classes in Newcastle University Medicine Malaysia (NUMed) were replaced with e-learning. Our study aims to explore students' e-learning experiences and its perceived benefits and challenges during the pandemic. Methods: 285 students recruited via convenience sampling participated in this cross-sectional study. Participants completed a self-administered online questionnaire on sociodemographic factors and experiences with e-learning. Descriptive statistics and Spearman's correlation tests were used to analyze the data. Results: Most students used laptops (n=275, 96.5%) for e-learning and owned at least two electronic devices (n=245, 86%). Over half our students (n=148, 51.9%) reported no change to theoretical knowledge, while about three-quarters (n=213, 74.7%) perceived practical skills to have worsened. Students preferred paper-based exams (n=170, 59.6%) and objectively formatted online exams (n=193, 67.7%). Since transitioning to e-learning, the majority of students (n=207, 72.6%) reported difficulties studying online and were unsatisfied with their academic performance (n=166, 58.2%). Students preferred e-learning due to the lower risk of contracting COVID-19 (n=256, 89.8%), the convenience of online classes (n=244, 85.6%) and flexible schedules (n=219, 76.8%). However, the lack of patient contact (n=236, 82.8%), lecturer and peer interaction (n=234, 82.1%), and unreliable internet (n=201, 70.5%) made e-learning challenging. Students' experiences were generally affected by multiple factors encompassing personal, lecturer, and environmental aspects. Conclusion: E-learning during the COVID-19 pandemic has negatively impacted students' practical skills and performance satisfaction. Therefore, the university should look towards addressing e-learning constraints and providing adequate support to improve students' educational experiences in the ongoing pandemic.